2021
DOI: 10.7554/elife.65759
|View full text |Cite
|
Sign up to set email alerts
|

RNF43 inhibits WNT5A-driven signaling and suppresses melanoma invasion and resistance to the targeted therapy

Abstract: RNF43 is an E3 ubiquitin ligase and known negative regulator of WNT/β-catenin signaling. We demonstrate that RNF43 is also a regulator of noncanonical WNT5A-induced signaling in human cells. Analysis of the RNF43 interactome using BioID and immunoprecipitation showed that RNF43 can interact with the core receptor complex components dedicated to the noncanonical Wnt pathway such as ROR1, ROR2, VANGL1, and VANGL2. RNF43 triggers VANGL2 ubiquitination and proteasomal degradation and clathrin-dependent internaliza… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 189 publications
(190 reference statements)
1
20
0
Order By: Relevance
“…Of note, we found no correlation of response with the presence of APC or CTNNB1 mutations or β-catenin protein expression or localization in mCRC BRAF-V600E tumors (Extended Data Fig. 9a–d and Supplementary Table 1 ), suggesting that noncanonical WNT pathways 34 , 35 , rather than canonical (β-catenin-dependent) signaling, might be involved in modulation of anti-BRAF/EGFR activity.…”
Section: Discussionmentioning
confidence: 81%
“…Of note, we found no correlation of response with the presence of APC or CTNNB1 mutations or β-catenin protein expression or localization in mCRC BRAF-V600E tumors (Extended Data Fig. 9a–d and Supplementary Table 1 ), suggesting that noncanonical WNT pathways 34 , 35 , rather than canonical (β-catenin-dependent) signaling, might be involved in modulation of anti-BRAF/EGFR activity.…”
Section: Discussionmentioning
confidence: 81%
“…Genetic alterations in WNT signaling molecules drive carcinogenesis in colorectal, gastric, liver, uterine and other cancers [ 6 ]. Loss-of-function alterations in the APC (adenomatous polyposis coli), AXIN1 and AXIN2 genes and gain-of-function mutations in the CTNNB1 (β-catenin) gene activate the canonical WNT signaling cascade owing to stabilization and nuclear accumulation of β-catenin [ 7 ], while loss-of-function alterations in the RNF43 (ring finger protein 43) gene can activate both canonical and noncanonical WNT signaling cascades through stabilization of plasma membrane Frizzled, LRP6 and ROR1 [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in melanoma cells, Vangl1 and Vangl2 interact with the E3 ubiquitin ligase RNF43. In this context, Vangl2 colocalizes with RNF43 at the plasma membrane and undergoes RNF43-mediated ubiquitination that results in Vangl2 proteasomal degradation and inhibition of Wnt5a-mediated cell invasion ( Radaszkiewicz et al, 2021 ). We ( Wald et al, 2017 ) and others ( Sun et al, 2017 ) have implicated Vangl as a scaffold for the E3 ubiquitin ligase Nrdp1, and have identified that the coiled-coil domain of Nrdp1 is critical for interaction with Vangl1 and Vangl2 ( Wald et al, 2017 ).…”
Section: Vangl As a Key Regulator Of Tumor Progressionmentioning
confidence: 99%